Collecting Deer Keds (Diptera: Hippoboscidae: Lipoptena Nitzsch, 1818 and Neolipoptena Bequaert, 1942) and Ticks (Acari: Ixodidae) From Hunter-Harvested Deer and Other Cervids. Issue 6 (2nd November 2020) - Poh, Karen C; Skvarla, Michael; Evans, Jesse R; Machtinger, Erika T
Abstract: Deer keds (Diptera: Hippoboscidae: Lipoptena Nitzsch, 1818 and Neolipoptena Bequaert, 1942) are blood-feeding ectoparasites that primarily attack cervids and occasionally bite humans, while ticks may be found on cervids, but are more generalized in host choice. Recent detection of pathogens such as Anaplasma and Borrelia in deer keds and historical infections of tick-borne diseases provides reason to investigate these ectoparasites as vectors. However, previous methods employed to sample deer keds and ticks vary, making it difficult to standardize and compare ectoparasite burdens on cervids. Therefore, we propose a standardized protocol to collect deer keds and ticks from hunter-harvested deer, which combines previous methods of sampling, including timing of collections, dividing sections of the deer, and materials used in the collection process. We tested a three-section and a five-section sampling scheme in 2018 and 2019, respectively, and found that dividing the deer body into five sections provided more specificity in identifying where deer keds and ticks may be found on deer. Data from 2018 suggested that deer keds and ticks were found on all three sections (head, anterior, posterior), while data from 2019 suggested that more Ixodes scapularis were found on the head and deer keds were found on all body sections (head, dorsal anterior, dorsal posterior, ventral anterior, and ventral posterior). The protocol provides an efficient way to sample deer for deer keds and ticks and allows researchers to compare ectoparasite burdens across geographical regions. Furthermore, this protocol can be used to collect other ectoparasites from deer or other cervids.